Optimizing Student-Centered Learning to Enhance Student Engagement in Christian Religious Education Classes (Grade X) at SMKN 2 Palangka Raya - Susida; Telhalia; Yuherlita Marneci (CV. Edujavare Publishing, 2026)
-